Penyerbukan Terkendali antar Individu Superior Melaleuca cajuputi sub sp Cajuputi di Kebun Benih Ponorogo - Noor Khomsah Kartikawati; Prastyono Prastyono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Controlled pollination is one of the important activities in a breeding program. This research was aimed to determinate reproductive success and general combining ability of superior individuals of cajuput (Melaleuca cajuputi subsp cajuputi) which having a high oil yield and oil content. The research was conducted during flowering season on December to June in seedling seed orchard of cajuput at Ponorogo. Ten parent trees from 4 provenances, namely Suli (Ambon), Pelita Jaya (Seram), Ponorogo (East Java) and Gundih (Central Java) were used in controlled pollination. Controlled pollination was carried out reciprocally with emasculation and isolation in pollination bag. The results showed that out of 28 crossed combinations, the best effective pollination found at crossing of individuals 25 x 60 (provenance Suli, Ambon x provenance Ponorogo). The best pollen donor was found no 25 from Suli, Ambon. While the best reproductive success was found in crossing individual 78 x 25 (provenance Ponorogo X Provenance Suli, Ambon).